Rare and Intermediate Taxa Shape the Gut Bacterial Structure in Neonates and Preterm Infants with Necrotizing Enterocolitis - Yu Wang; Qi Wang; Fengan Jia; Dan Li; Xuyang Gao; Xiaoge Zhang; Fan Chang; Yun Xie (Journal of microbiology and biotechnology, 2025)
Necrotizing enterocolitis (NEC) is a common neonatal gastrointestinal disease with high morbidity and mortality, especially in premature infants. In a prospective case-control study, we aimed to investigate the dynamic changes in the gut microbiota of preterm infants with NEC. Infants diagnosed with NEC and preterm neonates were enrolled in this study, while normal neonates were selected as the control group. The collected samples were divided into three groups: the control group (NC), the neonatal NEC group (NEC), and the premature delivery NEC group (pdNEC). Along with basic clinical data, fecal samples from the infants (n = 39) were collected at the time of the first diagnosis of NEC for 16S rRNA gene sequencing. Analysis of the gut microbiota revealed no significant difference in α-diversity between infants with NEC and controls, regardless of preterm birth. The significant difference in β-diversity was primarily driven by the rare and intermediate subgroups. The rare gut subgroup found in premature infants with NEC played a crucial role in the deterministic process and specialized functionality of the microbiota, ultimately forming a sparse association network structure. Finally, multiple biomarkers of Enterococcus from the Firmicutes phylum were identified, providing a theoretical basis for diagnosing NEC in premature infants.